Predictive Factors for Early Initiation of Artificial Feeding in Patients With Sporadic Creutzfeldt-Jakob Disease - Hsieh, Pei-Chen; Li, Han-Tao; Chang, Chun-Wei; Wu, Yih-Ru; Kuo, Hung-Chou (Frontiers in Neurology, 2018)
Background: Akinetic mutism has often been used as the predictor of sporadic Creutzfeldt-Jacob disease (sCJD) endpoints, but it may be difficult for general physcians to assess. Nasogastric (NG) tube insertion is indicated for many neurodegenerative diseases with a clinical course of swallowing failure, and can be more easily identified than akinetic mutism by general physicians. Therefore, the aim of this study was to identify whether there are predictive factors for early initiation of artificial feeding in patients with sCJD who require enteral nutrition due to swallowing failure. Methods: We retrospectively reviewed the medical records of all patients diagnosed with probable sCJD who were admitted to the neurology ward at a medical center in Taiwan from January 2002 to July 2017. We used Pearson’s chi-squared test to detect the correlation of initial symptoms, neurological signs, brain magnetic resonance imaging (MRI), electroencephalography (EEG), and increased levels of 14-3-3 protein in cerebrospinal fluid (CSF) analysis. The Cox proportional hazards model was used to detect prognostic factors for early initiation of NG tube insertion in sCJD patients. Results: The onset age ranged from 51 to 83 years, and mostly ranged from 60 to 79 years. Akinetic mutism was correlated with pyramidal tract signs, myoclonus, and extrapyramidal signs. Furthermore, myoclonus was revealed to be associated with pyramidal tract signs. Multivariate Cox regression analysis showed that myoclonus and elevated CSF levels of 14-3-3 protein are predictive of early NG insertion. Conclusions: Increased levels of 14-3-3 protein in CSF and the presence of myoclonus at diagnosis are predictive of early swallowing difficulty and indicate rapid deterioration in probable sCJD. In addition to akinetic mutism, early initiation of artificial feeding can be used to predict early deterioration in sCJD.